Gold-catalyzed dehydrazinative C(sp)-S coupling reactions of arylsulfonyl hydrazides with ethynylbenziodoxolones for accessing alkynyl sulfones - Shinde, Popat S.; Patil, Nitin T. (European Journal of Organic Chemistry, 2017)
A gold(III)-catalyzed dehydrazinative coupling reaction between arylsulfonyl hydrazides and ethynylbenziodoxolone reagents was realized for the synthesis of alkynyl sulfones. The scope and versatility of the reaction were demonstrated by the efficient synthesis of 23 derivatives with diverse structural features.